2009
DOI: 10.1056/nejmoa0802556
|View full text |Cite
|
Sign up to set email alerts
|

Male Circumcision for the Prevention of HSV-2 and HPV Infections and Syphilis

Abstract: BACKGROUND Male circumcision significantly reduced the incidence of human immunodeficiency virus (HIV) infection among men in three clinical trials. We assessed the efficacy of male circumcision for the prevention of herpes simplex virus type 2 (HSV-2) and human papillomavirus (HPV) infections and syphilis in HIV-negative adolescent boys and men. METHODS We enrolled 5534 HIV-negative, uncircumcised male subjects between the ages of 15 and 49 years in two trials of male circumcision for the prevention of HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
382
7
19

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 463 publications
(422 citation statements)
references
References 40 publications
14
382
7
19
Order By: Relevance
“…68 An additional cohort study with fair evidence found that circumcised men were significantly less likely to have active syphilis at the point of study recruitment; when the men were followed up prospectively for 2 years, a protective effect was also observed but was nonsignificant. 69 Good evidence from a large RCT reported no reduction or trend toward reduction for male circumcision and the incidence of syphilis 71 ; however, the extent to which protection might be afforded, and among which specific populations, is difficult to determine. One meta-analysis with good evidence found some protective effect of circumcision against HSV-2 of borderline statistical significance.…”
Section: Ulcerative Stismentioning
confidence: 99%
See 2 more Smart Citations
“…68 An additional cohort study with fair evidence found that circumcised men were significantly less likely to have active syphilis at the point of study recruitment; when the men were followed up prospectively for 2 years, a protective effect was also observed but was nonsignificant. 69 Good evidence from a large RCT reported no reduction or trend toward reduction for male circumcision and the incidence of syphilis 71 ; however, the extent to which protection might be afforded, and among which specific populations, is difficult to determine. One meta-analysis with good evidence found some protective effect of circumcision against HSV-2 of borderline statistical significance.…”
Section: Ulcerative Stismentioning
confidence: 99%
“…73 In the Uganda study, the risk of HSV-2 infection (adjusted for other factors) was 28% lower in circumcised men. 71 There is fair evidence from 1 study that male circumcision protects female partners against HSV-2 infection. 33 Two studies with fair evidence found that there is no effect of circumcision on the risk of HSV-2 acquisition.…”
Section: Ulcerative Stismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent randomised control trials have reported beneficial effects of circumcision on HPV acquisition and clearance in males in Africa. 82,84,86 However, Van Howe has suggested that these results can be completely explained by sampling bias 87 and has highlighted inadequacies in the methods used for sampling the penis in another study. 80,81 The evidence for whether condoms are a highly effective barrier against transmission of HPV between partners is conflicting.…”
Section: Are Circumcision and Condoms Protective Against Infection?mentioning
confidence: 99%
“…A variety of studies have been conducted to investigate the effectiveness of circumcision in the prevention of HPV infection [78][79][80][81][82][83][84][85][86][87][88] and the interpretation of the findings from these is currently under debate. Recent randomised control trials have reported beneficial effects of circumcision on HPV acquisition and clearance in males in Africa.…”
Section: Are Circumcision and Condoms Protective Against Infection?mentioning
confidence: 99%